2017
DOI: 10.1111/codi.13581
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the incidence of early endoscopic recurrence after ileocolonic resection for Crohn's disease: a multicentre observational study

Abstract: This study found that only preoperative steroid use was a significant risk factor for EPER after ileocolonic resection for CD. Prospective studies are necessary to evaluate precisely the impact of perioperative medications on EPER rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…According to the authors of the former study, this could be partially explained by the small number of patients recruited (n=127), including only 15% smokers. As for the latter, this result could be explained by the lack of 23% and 16% of smoking data at diagnosis and follow up respectively [ 43 , 44 ].…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the authors of the former study, this could be partially explained by the small number of patients recruited (n=127), including only 15% smokers. As for the latter, this result could be explained by the lack of 23% and 16% of smoking data at diagnosis and follow up respectively [ 43 , 44 ].…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…It has been evaluated in several studies, but outcomes are conflicting. Searching the literature, we found studies demonstrating either male [ 49 ] or female [ 50 ] sex as a predictive factor for POR, whereas the majority of authors found no differences in recurrence rates [ 43 , 44 , 51 , 52 ].…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This high risk of postoperative relapse and reoperation is significantly reduced if a patient quits smoking[ 4 ]. A recently published study only identified preoperative steroid use as a risk factor for early postoperative endoscopic recurrence[ 5 ], while another study found a higher risk for postoperative endoscopic recurrence in case of previous use of two or more anti-tumor necrosis factor (TNF)-α agents[ 6 ].…”
Section: Introductionmentioning
confidence: 99%